2020
DOI: 10.1371/journal.ppat.1008685
|View full text |Cite
|
Sign up to set email alerts
|

Ectromelia-encoded virulence factor C15 specifically inhibits antigen presentation to CD4+ T cells post peptide loading

Abstract: Smallpox and monkeypox pose severe threats to human health. Other orthopoxviruses are comparably virulent in their natural hosts, including ectromelia, the cause of mousepox. Disease severity is linked to an array of immunomodulatory proteins including the B22 family, which has homologs in all pathogenic orthopoxviruses but not attenuated vaccine strains. We demonstrate that the ectromelia B22 member, C15, is necessary and sufficient for selective inhibition of CD4 + but not CD8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…With the addition of this novel NK-inhibitory function, we have now revealed that in murine cells C15 is able to inhibit NK and CD4 T cell but not CD8 T cell contact and function. While the specific molecular mechanism of C15 antagonism of CD4 T cells remains to be determined, it appears to impact the formation of immunological synapses (Forsyth et al, 2020). Although there are significant distinctions between T cell and NK cell synapses, these contact-dependent interaction sites are also implicated by results shown here.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…With the addition of this novel NK-inhibitory function, we have now revealed that in murine cells C15 is able to inhibit NK and CD4 T cell but not CD8 T cell contact and function. While the specific molecular mechanism of C15 antagonism of CD4 T cells remains to be determined, it appears to impact the formation of immunological synapses (Forsyth et al, 2020). Although there are significant distinctions between T cell and NK cell synapses, these contact-dependent interaction sites are also implicated by results shown here.…”
Section: Resultsmentioning
confidence: 99%
“…B22 family members are well conserved across the virulent OPXVs (including VARV, MPXV and ECTV), but the C15 ORF is truncated in VACV. The size and conservation of B22 family members suggest a large contribution to virulence, and this has been demonstrated for the homologs in MPXV and ECTV (Alzhanova et al, 2014; Reynolds et al, 2017; Forsyth et al, 2020). Functionally, B22 family members have been shown to modulate T cell responses via complex mechanisms.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations